Giant coronary artery aneurysms in juvenile polyarteritis nodosa: a case report - Canares Therese L; Wahezi Dawn M; Farooqi Kanwal M; Pass Robert H; Ilowite Norman T (BMC, 2012)
Abstract Juvenile polyarteritis nodosa (PAN) is a rare, necrotizing vasculitis, primarily affecting small to medium-sized muscular arteries. Cardiac involvement amongst patients with PAN is uncommon and reports of coronary artery aneurysms in juvenile PAN are exceedingly rare. We describe a 16 year old girl who presented with fever, arthritis and two giant coronary artery aneurysms, initially diagnosed as atypical Kawasaki disease and treated with IVIG and methylprednisolone. Her persistent fevers, arthritis, myalgias were refractory to treatment, and onset of a vasculitic rash suggested an alternative diagnosis. Based on angiographic abnormalities, polymyalgia, hypertension and skin involvement, this patient met criteria for juvenile PAN. She was treated with six months of intravenous cyclophosphamide and high dose corticosteroids for presumed PAN related coronary vasculitis. Maintenance therapy was continued with azathioprine and the patient currently remains without evidence of active vasculitis. She remains on anticoagulation for persistence of the aneurysms. This case illustrates a rare and unusual presentation of giant coronary artery aneurysms in the setting of juvenile PAN.